Dendrology the study of trees - CEV Multimedia ([United States] : CEV Multimedia, 2009)
'In order to properly realize the economical usefulness of woody plants, it is important to understand identification and horticultural properties. This presentation details tree anatomy (i.e., leaves, trunk, branches and roots), providing form and function of each'
Title from container
Registration codes : 657115-60533325-393482
Distributed by Insight Media'CEV70405'
Executive producers : Gordon Davis, Jeff Landsdell ; production manager : Dusty Moore
System requirements: Adobe Acrobat Reader; Win 2000/XP/Vista, Mac OSX
Keywords: Trees